KOMUNITAS BELAJAR “QARYAH THAYYIBAH” DALAM PERSPEKTIF PENDIDIKAN PEMBEBASAN PAULO FREIRE. (Forum Ilmu Sosial, 2015)
Qaryah Thayyibah learning communities in Kalibening ,Tingkir, Salatiga is one form of community-based alternative schools. As institutionally, curriculum planning, implementation methods of education, and alternative methods of evaluation. Qaryah Thayyibah learning community providing equal education program package B (equivalent to junior high school) and package C (equivalent to high school). The process of applied learning and evoked responses citizens to learn after participating in the learning process that is applied in the Community Learning Qaryah Thayyibah are very important.  From the data obtained in the study, showed that the learning process is applied in Qaryah Thayyibah based learning community agreement includes planning, implementation, and evaluation, the companion function only as a facilitator. The response form that appears on citizens studying in Qaryah shows Thayyibah more positive direction as seen from the few changes in behavior and mindset.